In This Fragile World Swahili Poetry of Commitment by Ustadh Mahmoud Mau - Mau, Ustadh Mahmoud (Brill, 2023)
The present volume is a pioneering collection of poetry by the outstanding Kenyan poet, intellectual and imam Ustadh Mahmmoud Mau (born 1952) from Lamu island, once an Indian Ocean hub, now on the edge of the nation state. By means of poetry in Arabic script, the poet raises his voice against social ills and injustices troubling his community on Lamu. The book situates Mahmoud Mau's oeuvre within transoceanic exchanges of thoughts so characteristic of the Swahili coast. It shows how Swahili Indian Ocean intellectual history inhabits an individual biography and writings. Moreover, it also portrays a unique African Muslim thinker and his poetry in the local language, which has so often been neglected as major site for critical discourse in Islamic Africa. The selected poetry is clustered around the following themes: jamii: societal topical issues, ilimu: the importance of education, huruma: social roles and responsabilities, matukio: biographical events and maombi: supplications. Prefaced by Rayya Timamy (Nairobi University), the volume includes contributions by Jasmin Mahazi, Kai Kresse and Kadara Swaleh, Annachiara Raia and Clarissa Vierke. The authors' approaches highlight the relevance of local epistemologies as archives for understanding the relationship between reform Islam and local communities in contemporary Africa.